Correction of Transposition of Great Arteries with Ventricular Septal Defect and Left Outflow Tract Obstruction with Double Arterial Translocation with Preservation of the Pulmonary Valve - Furlanetto, Gláucio; Furlanetto, Beatriz H. S. (IntechOpen, 2011)
None